2018
DOI: 10.1016/j.ijresmar.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Investor sentiment and advertising expenditure

Abstract: A strategic issue facing marketing managers is 'how much and when' to spend on advertising. We argue that investor sentiment in the stock market may influence advertising expenditure by affecting firms' ability to raise new funds. We show that during periods of low (high) investor sentiment, firms decrease (increase) their advertising expenditure, even though the effectiveness of advertising is greater (lower) during such periods. We also find that these results are stronger for financially constrained firms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 64 publications
(101 reference statements)
0
12
0
1
Order By: Relevance
“…We extended our search to identifying the correlation between sentiment and innovation investment. Our study showed that, negative sentiment causes higher innovation investment whilst most previous research works focused on the statistical significance of sentiment on innovation investment as well as the impact of sentiment on other financial variables (Tri & Zhaoxia, 2016;Daniel, 2016;Mujtaba, Piyush, & Ferdinand, 2018;Tanya, Samuel, & Francisco, 2018). Our findings provide an adequate information for firms" making innovation-investment decisions.…”
Section: Theoretical Contributions Of Our Studymentioning
confidence: 46%
See 1 more Smart Citation
“…We extended our search to identifying the correlation between sentiment and innovation investment. Our study showed that, negative sentiment causes higher innovation investment whilst most previous research works focused on the statistical significance of sentiment on innovation investment as well as the impact of sentiment on other financial variables (Tri & Zhaoxia, 2016;Daniel, 2016;Mujtaba, Piyush, & Ferdinand, 2018;Tanya, Samuel, & Francisco, 2018). Our findings provide an adequate information for firms" making innovation-investment decisions.…”
Section: Theoretical Contributions Of Our Studymentioning
confidence: 46%
“…Thus, during the periods when market participants are more rational, high returns will lead to increased innovation activities in the firm. Mujtaba, Piyush, and Ferdinand (2018) showed that, investor sentiment can influence firm"s advertising expenditure. They found that, during periods of low (high) investor sentiment, firms decrease (increase) their advertising expenditure, even though the effectiveness of advertising is greater (lower) during such periods.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Marketing expenditures are not only shortterm expenditures but also long-term investments for a company since marketing activities contribute to the firm's brand equity that will improve the profit margin, current and future earnings (Graham & Frankenberger, 2011). Payoffs of advertising expenditures can be viewed as uncertain and accruing over a long time, but advertising expenditures, namely marketing investments on brand equity have significant impact on financial measures (Grullon et al, 2004;Mian et al, 2018;Sydney-Hilton &Vila-Lopez, 2019). In a company, marketing expenditures may exceed capital expenditures and although companies do not disclose marketing expenditures as consistently as financial expenditures, marketing expenditures are effective on future sales and market value of a company (Herremans & Ryans, 1995;Sydney-Hilton &Vila-Lopez, 2019).…”
Section: The Impact Of Marketing Activities On Business Performance Imentioning
confidence: 99%
“…Hal tersebut juga mengindikasikan kinerja perusahaan akan melemah ketikan manajemen laba terus di lakukan. Selain penjualan, hal lain yang dapat meningkatkan beban iklan dalam beban diskresional adalah intuisi investor (Mian, dkk., 2018). Khususnya untuk perusahaan yang menitikberatkan pada pendanaan eksternal, beban iklan menjadi penting untuk meningkatkan nilai perusahaan di mata investor.…”
Section: Pengaruh Abnormal Beban Diskresional Terhadap Kinerja Perusaunclassified